Реабілітаційні заходи у хворих з мозковим півкульним ішемічним інсультом у ранній відновний період - Мєдвєдкова, Світлана Олександрівна; Medvedkova, S. O. (My University, 2018)
Мета — удосконалити лікувально-реабілітаційні заходи у хворих, які перенесли мозковий півкульний ішемічний інсульт, шляхом розподілу їх на клініко-реабілітаційні групи з використанням сучасних шкал для диференційованого підходу до відновного лікування. Матеріали і методи. Проведено комплексне дослідження з використанням шкали NIHSS, індексу Б артел (ІБ), модифікованої шкали Р енкіна (МШР) на 10, 30, 90 і 180-ту добу захворювання та комп’ютерної томографії головного мозку, а також реабілітаційне лікування 375 хворих (270 чоловіків та 105 жінок, середній вік — (58,36 ± 0,42) року), які перенесли мозковий півкульний ішемічний інсульт та перебували у ранньому відновному періоді захворювання. Пацієнтів розподілили на чотири групи. У першу групу залучено 127 (33,9 %) хворих з легким ступенем післяінсультних розладів (NIHSS ≤ 7 балів, ІБ > 75 балів, МШР — 1 — 2 бали) без супутньої соматичної патології, у другу — 157 (41,9 %) хворих з легким ступенем післяінсультних розладів (NIHSS ≤ 7 балів, ІБ > 75 балів, МШР — 1 — 2 бали) та супутньою соматичною патологією, у третю групу — 47 (12,5 %) хворих з помірними та вираженими післяінсультними розладами (NIHSS > 7 балів, 45 < BI < 75 балів, МШР — 3 — 4 бали) без супутньої соматичної патології, у четверту групу — 44 (11,7 %) хворих з помірними та вираженими післяінсультними розладами (NIHSS > 7 балів, 45 < BI < 75 балів, МШР — 3 — 4 бали) і супутньою соматичною патологією. Objective — to improve the therapeutic and rehabilitation measures in patients who have undergone cerebral ischemic hemispheric stroke by dividing them into clinic and rehabilitation groups, using modern scales, for a differentiated approach to rehabilitation. Methods and subjects. We have done a complex research and rehabilitation treatment for 375 patients (270 men and 105 women, the average age is 58.36 ± 0.42 years), after cerebral ischemic hemispheric stroke and they were in early recovery period of disease, using computed tomography of the brain, NIHSS, I B, mRS on the 10th, 30th, 90th and 180th day of disease. Statistical analysis was done using descriptive statistics methods. The presence of the relationship between qualitative features was evaluated by the Pearson chi-square test. Patients were distributed into 4 groups. 127 patients (33.9 %) with CIHS were included in the first clinic-rehabilitation group where the degree of severity of poststroke disorders was mild (state by scales NIHSS ≤ 7 points, BI > 75 points, mRS 1 — 2 points); concomitant pathology was absent. The second clinic-rehabilitation group consisted of 157 patients (41.9 %), the degree of severe of post-stroke disorders was mild; (state by the scales: (NIHSS ≤ 7 points, BI > 75 points, mRS 1 — 2 points), concomitant somatic pathology was presented. The third CRG included 47 patients (12.5 %) with CIHS, where the severity of post-stroke disorders was moderate and severe (state by scales: NIHSS > 7 points, BI > 45, but < 75 points, mRS 3 — 4 points); concomitant pathology was absent. The fourth clinical and rehabilitation group included 44 patients (11.7 %), where the degree the severity of post-stroke disorders was moderate and severe (state on scales: NIHSS > 7 points, BI > 45, but < 75 points, mRS 3 — 4 points); concomitant somatic pathology was presented.
Rehabilitation measures among the patients with cerebral ischemic hemispheric stroke in early recovery period
Keywords: ішемічний інсульт; клініко-реабілітаційні групи; комплексні реабілітаційні заходи; ischemic stroke; clinical and rehabilitation groups; complex rehabilitation measures